2003
DOI: 10.2746/042516403776114243
|View full text |Cite
|
Sign up to set email alerts
|

Spasmogenic action of endothelin‐1 on isolated equine pulmonary artery and bronchus

Abstract: Summary Reasons for performing study: There is currently little published information about the effects of endothelin‐1 (ET‐1), a potent endogenous spasmogen of vascular and airway smooth muscle, on pulmonary vasculature and airways or which ET receptor subtypes mediate ET‐1‐induced vasoconstrictive and bronchoconstrictive action in the horse. Objectives: To investigate the effect of endothelin‐1 (ET‐1) on smooth muscle from isolated equine pulmonary artery and bronchus. In addition, the roles of ETA and ETB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Increased MPAP and decreased Pao 2 were also associated with increased plasma ET-1 concentrations in endotoxemic pigs. 13 Endothelin-1 is also a potent vasoconstrictor in the pulmonary vessels in horses 24,25 and could potentially contribute to hypoxia in anesthetized horses. However, plasma ET-1 concentrations did not change at any time during the study of this report, which could explain the lack of a rebound effect.…”
Section: Discussionmentioning
confidence: 99%
“…Increased MPAP and decreased Pao 2 were also associated with increased plasma ET-1 concentrations in endotoxemic pigs. 13 Endothelin-1 is also a potent vasoconstrictor in the pulmonary vessels in horses 24,25 and could potentially contribute to hypoxia in anesthetized horses. However, plasma ET-1 concentrations did not change at any time during the study of this report, which could explain the lack of a rebound effect.…”
Section: Discussionmentioning
confidence: 99%
“…The C group of horses, which were more hypoxaemic than the NO group at all time points also had higher ET‐1 concentrations at all time points, although the variability of the measurements was high and significance was only reached at Times 2, 20 and 25. Endothelin‐1 is also a potent vasoconstrictor in the pulmonary vessels in horses (Benamou et al. 2001, 2003) and ET‐1 increases in horses known to have recurrent airway obstruction (Benamou et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that differences between species or technique could account for our inability to detect antagonism by these drugs. Indeed, up to now, blocking of ET B -receptors in the different vascular beds of the horse has been unsuccessful (Benamou et al 2003;Katz et al 2003). It has also been reported that the blockade of ET B -receptors in other species does not always result in an alteration of vasomotor tone (Pang et al 1998;Lipa et al 1999;Leslie et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All solutions were equilibrated to room temperature (22°C) prior to injection. The concentrations of ET-1, antagonists and PHE were based on in vitro and in vivo vascular dose-response studies (Elliott et al 1994;Lawrence and Brain 1994;Pang et al 1998;Lipa et al 1999;Katugampola et al 2000;Venugopal et al 2001;Benamou et al 2003;Katz et al 2003;Bowen et al 2004;Wilson et al 2004).…”
Section: Preparation Of Solutions For Intradermal Injectionmentioning
confidence: 99%